Деревообробка у давньоруському місті Воїнь - Сергєєва, М. С. (Давнина. Харківський історико-археологічний щорічник, 1970)
РезюмеСергеева М. С. Деревообработка в древнерусском городе ВоиньВ статье рассматриваются материалы по деревообработке, найденные во время раскопок городища Воинская Гребля. Среди них орудия труда, крепежные детали (гвозди, скобы, корабельные заклепки), металлические детали деревянных предметов и значительное количество деревянных изделий.Сырьевой базой для деревообработки были местные породы дерева. В строительстве использовали дуб, реже — сосну, столовая посуда изготовлена из клена и ясеня. Найдено несколько толстостенных резных сосудов из липы. Материалом для изготовления предметов домашнего обихода служил ясень, для ткацких орудий — клен.Термин «деревообработка» объединяет несколько ремесленных специальностей, связанных только использованием одинакового сырья. Правомерно говорить об отдельных деревообрабатывающих ремеслах. Зафиксирована деятельность плотников, включая судостроителей, бондарей, резчиков по дереву и токарей.Ключевые слова: Среднее Поднепровье, Древняя Русь, древнерусское ремесло, деревообработка, резьба по дереву. SummaryM. Sergeyeva. Woodworking in Old Russian Town VoinThe article deals with materials on woodworking found during the excavation of Voyinska Grebl ya hillfort. Among them are tools, fixings (nails, staples, ship rivets), metal parts of wooden objects a significant number of wood products also was detected above all things there were fragments of wooden utensils of 12th century. In addition remnants of barrels, household items, fragmented handle of a knife, tools (shuttle, spindle, weaving comb) were found.Analyses of the wood showed, that the raw materials for woodworking was local wood. In construction an oak, and less often a pine were used, tableware was made from maple and ash. There are several thick-walled carved vessels of linden. Material for household items was ash, and for weaving tools it was maple.The term of woodworking unites several different craft specialties, related only to the use of the same raw materials. It is correct to speak about individual woodworking crafts. The work of carpenters, including shipbuilders, coopers, woodcarvers, and turners was recorded.Key words: Middle Dnieper area, Old Rus, Old Russian handicraft, woodworking, wood carving.